SPACE INNOVATIONS IN ARCHITECTURAL DESIGN AND THEIR IMPACT ON UKRAINE’S POST-WAR RECONSTRUCTION - Antonenko, Ihor; Ahliullin, Ruslan (Theory and practice of design, 2025)
This article explores the integration of space technologies into Ukrainian architectural design as a means of enhancing the resilience and efficiency of construction during post-war recovery. It examines international and domestic experiences, including projects such as modular lunar stations, 3D and 4D printing, the use of smart materials, and the adaptation of vernacular architecture principles. The study analyzes the application potential of closed-loop systems, in-situ resource utilization (ISRU), Building Information Modeling (BIM), and online construction platforms in architectural practice. The article also highlights the role of Ukrainian designers and researchers in the global context of applying space innovations in construction, emphasizing the importance of modularity, energy efficiency, and materials science in improving the quality of the built environment. Purpose. The aim of this study is to investigate the process of implementing space technologies into Ukrainian architectural design and to explore how this implementation can contribute to the reconstruction of war-damaged structures in Ukraine. Methodology. The research employs informational-investigative and visual-analytical approaches, combined with methods of systematization and comparative analysis regarding the use of space technologies in architectural design. Results. The study discusses the integration process of space innovations into Ukrainian architectural design, their impact on improving the reliability and adaptability of design objects, methods for their transformation, and their potential use in modular vernacular architecture, which often relies on local resources and techniques. It outlines possibilities and strategies for applying these technologies in the context of Ukraine’s post-war rebuilding. Scientific novelty. The study examines the practical application of space technologies in Ukrainian architectural design, identifies implementation features and challenges, and contributes to a deeper understanding of their integration into the design process. Practical relevance. The findings may prove useful for developing design methods and strategies, as well as for educational and research purposes among students, instructors, and architects in the field of design.